Determinants of subjective well-being among migrant and local elderly in China: a cross-sectional study - Chonghua Wan; Rassamee Sangthong; Liu Yuxi; Thammasin Ingviya (BMJ Open)
Objectives The study aimed to examine the association between individual and community levels in relation to subjective well-being (SWB) among the migrant and local elderly. It particularly focuses on the extent to which and the ways in which the residential environment of migrant and local elderly influences their SWB.Design A cross-sectional study.Setting Our study was conducted in Dongguan City, China.Participants Two groups of elderly (aged >60 years), including migrants and local residents, were recruited. A total of 470 migrants and 422 local residents participated in this study.Main outcome measures SWB was assessed by the Memorial University of Newfoundland Scale of Happiness.Results The community-level health facility density had a positive association with SWB (B=0.38, p<0.01), whereas the financial facility density had a negative association (B=−0.42, p<0.01). The density of health and financial facilities affected the local elderly more than the migrant elderly. Social cohesion is an aspect of the social environment of the community that influenced elders’ SWB (B=0.72, p<0.001).Conclusions The primary determinants of SWB for both the migrant and local elderly included individual, societal and environmental factors.